Experimental investigation of full solar spectrum utilization based on nanofluid spectral splitter for greenhouse applications. (15th February 2022) - Yuan, Yu; Fang, Hui; Wu, Gang; Yang, Qichang; Ma, Qianlei; Ji, Yaning; Cheng, Ruifeng; Zhang, Yi; Tong, Yuxin
Highlights: The nanofluid-based spectral splitter can achieve ideal light environment for plant growth. The synthesized nanofluids can transmit light at wavelengths of 300 ∼ 800 nm while absorb solar energy at 800 ∼ 1500 nm. The total utilization efficiency reaches more than 73% together with a crop growth factor of 93.6%. The annual output power of the proposed system reaches 358.9 kWh/m 2 . Abstract: According to its application, solar spectrum can be divided into plant active spectrum (PAS) (300 ∼ 800 nm) and heat active spectrum (HAS) (800 ∼ 1500 nm). PAS is absorbed by plants for photosynthesis, and HAS will cause indoor high temperature when entering the greenhouse, which is unfavorable to plants. Nanofluid-based spectral splitter (NSS) is an effective way to improve the full-spectrum utilization of solar energy because of its superior performance of high transmittance in PAS and strong absorption in HAS. In this study, ATO-WO3 /H2 O nanofluids (NFs) are synthesized, in which the nanoparticles (NPs) are composed of 2.4 vol% ATO and 97.6 vol% WO3 (ATO-WO3 ). Physical property analysis shows that the NPs are well-dispersed in the fluid. The average transmittance of 0.005 vol% ATO-WO3 NFs with 10 mm optical path-length is 79.56% in PAS and 24.22% in HAS. The photothermal efficiency of NSS is related to the thickness and flow rate of NFs. The outdoor experimental results show that the total solar utilization efficiency of NSS is higher than 73% under the condition of 10 mm thick NFs layer and 100 L/h flow rate. Among them, the photothermal conversion efficiency is 34.4%, and the annual output power is 358.9 kWh/m 2 . Meanwhile, the light use efficiency is 39.2%, and the defined crop growth factor is 93.6%. In addition, the NSS system has a payback period of 0.76 years and a levelized cost of energy of 0.041 /kWh within a 10-year life cycle. It shows that NSS greenhouse is feasible in technical and economic aspects. This study broadens the application of NFs in greenhouse and is an effective method to improve the full-spectrum utilization of solar energy.